Acanthamoeba species isolated from marine water in Malaysia exhibit distinct genotypes and variable physiological properties. (23rd November 2021) - Mohd Hussain, Rosnani Hanim; Abdul Ghani, Mohamed Kamel; Khan, Naveed Ahmed; Siddiqui, Ruqaiyyah; Anuar, Tengku Shahrul
Abstract: The present study identifies the Acanthamoeba genotypes and their pathogenic potential in five marine waters in Malaysia. Fifty water samples were collected between January and May 2019. Physical parameters of water quality were measured in situ, whereas chemical and microbiological analyses were conducted in the laboratory. All samples had undergone filtration using nitrocellulose membrane and were tested for Acanthamoeba using cultivation and polymerase chain reaction by targeting the 18S ribosomal RNA gene. The pathogenic potential of all positive isolates was identified using physiological tolerance tests. Thirty-six (72.0%) samples were positive for Acanthamoeba . Total coliforms ( p = 0.013) and pH level ( p = 0.023) displayed significant correlation with Acanthamoeba presence. Phylogenetic analysis showed that 27 samples belonged to genotype T4, four (T11), two (T18) and one from each genotype T5, T15 and T20. Thermo- and osmo-tolerance tests signified that three (8.3%) Acanthamoeba strains displayed highly pathogenic attributes. This study is the first investigation in Malaysia describing Acanthamoeba detection in marine water with molecular techniques and genotyping. The study outcomes revealed that the marine water in Malaysia could be an integral source of Acanthamoeba strains potentially pathogenic in humans. Thus, the potential risk of this water should be monitored routinely in each region. HIGHLIGHTS: First report on Acanthamoeba genotypic distribution in marine water, Malaysia. Highly pathogenic Acanthamoeba strain T4 was attributed. Total coliforms and pH level displayed a correlation with Acanthamoeba presence.